Harmonization of Customary Law and Islamic Family Law in the Tradition of Temu Ahak - Basrul Basrul; Ahmad Zuhdi (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study examines the harmonization of customary law and Islamic family law within the tradition of Temu Ahak in Indonesian marriage practices. Using a qualitative method with an empirical juridical approach through case studies, data were collected via interviews, observation, and documentation. The findings reveal that Temu Ahak functions as a socio-legal mechanism that provides space for deliberation, verification, and assessment of the readiness of prospective spouses, with the tengganai serving as the customary authority. The approval of the tengganai influences marriage administration, affirming Temu Ahak as a form of living law that interacts with formal law. From the perspective of Islamic family law, Temu Ahak reflects the principle of caution (ihtiyat) and responsibility in choosing a spouse, while in the framework of maqashid al-shari’ah it contributes to safeguarding religion, lineage, and honor. Thus, Temu Ahak represents a bridge of harmonization between customary norms, Islamic law, and state law in the marriage practices of society.